Irish writing London. - Herron, Tom (Bloomsbury studies in the city., 2013)
The presence of Irish writers is almost invisible in literary studies of London. The Irish Writing London redresses the critical deficit. A range of experts on particular Irish writers reflect on the diverse experiences and impact this immigrant group has had on the city. Such sustained attention to a location and concern of Irish writing, long passed over, opens up new terrain to not only reveal but create a history of Irish-London writing. Alongside discussions of Wilde, Shaw, Joyce and Yeats, the writing of the political nationalist Katharine Tynan and work of Irish-Language writer Ó Conair.